Data Driven Decision making concept - K. Kishore (AG Volumes, 2021)
The Decision-making based on solid facts as well as intelligence is referred to as the strategic data-based decision making. Unlike intuition-based decision making, in which judgments are made based on unsubstantiated opinions about the company and also its external environment, one such approach is based on facts and data. Data-driven strategic decision-making is indeed a popular recommendation for boosting efficiency as well as competitiveness, as well as ensuring responsibility to the public and shareholders. Strategic decision-making based on the data necessitates extensive data collecting and impartial analysis. Data-driven organisations are attempting to improve their decision-making abilities in the current age of big data. There is, meanwhile, a dearth of studies examining the capabilities of the (DDDM) data-driven decision making. There are four methods to defining capabilities: an unrelated, an unidirectional, entangled and mixed. DDDM capacity is then defined as a multi-dimensional construct using the procedure entanglement method.